A multicenter, open-label, phase III study of Abcertin in Gaucher disease. Issue 45 (November 2017) - Lee, Beom Hee; Abdalla, Ahmed Fathy; Choi, Jin-Ho; Beshlawy, Amal El; Kim, Gu-Hwan; Heo, Sun Hee; Megahed, Ahmed Megahed Hassan; Elsayed, Mona Abdel Latif; Barakat, Tarik El-Sayed Mohammad; Eid, Khaled Mohamed Abd El-Azim; El-Tagui, Mona Hassan; Mahmoud, Mona Mohamed Hamdy; et al.
Abstract: Background: Gaucher disease (GD) is caused by a deficiency in the lysosomal enzyme glucocerebrosidase. Enzyme replacement therapy (ERT) is recommended for clinical improvement. Methods: The efficacy and safety of a new imiglucerase, Abcertin, were assessed in 7 Egyptian patients with treatment-naïve type 1 GD. Each patient was administered a biweekly 60 U/kg dose of Abcertin for 6 months. The primary endpoint was the change in hemoglobin concentration. The secondary endpoints were changes from baseline in platelet counts, spleen and liver volumes, biomarker levels, skeletal parameters, and bone mineral density. Results: The hemoglobin concentration increased by a mean of 1.96 ± 0.91 g/dL (range 1.11–2.80 g/dL) or 20.6% ( P  = .001). Statistically significant increases in the platelet count and decreases in the spleen volume and biomarker levels were also observed. There were no severe drug-related adverse events. One patient developed anti-imiglucerase antibodies without neutralizing activity. Conclusion: Our study results demonstrate the efficacy and safety of Abcertin in patients with type 1 GD. This suggests that Abcertin can be an alternative ERT option for type 1 GD.